Effectiveness of An Active Learning Intervention on Enhancing the Knowledge and Attitude for Mitigating Health Risks among Electronic Waste Dismantling Workers: A Study in Buriram Province, Thailand - Sahanavin, Narut; Intrakun, Siriphat; Lertvarayut, Teepapipat; Santawee, Nuttapong; Phoyen, Kitti; Chetwittayachan, Tassanee (Journal of Posthumanism, 2025)
E-waste dismantling workers are exposed to various occupational hazards, including inhalation and dermal contact with hazardous substances, and musculoskeletal injuries due to improper work postures. Educational interventions are essential in mitigating these risks by improving knowledge and promoting positive attitudes toward safety practices. This study employed a one-group pretest–posttest design to evaluate the effectiveness of an active learning intervention among e-waste dismantling workers in Daeng Yai Sub-district, Ban Mai Chaiyaphot District, and Ban Pao Sub-district, Phutthaisong District, Buriram Province, Thailand. A total of 99 workers participated in a structured training program covering health risk prevention practices. Data was collected using pre- and post-education questionnaires and analyzed using a paired sample t-test at 0.01 and 0.001 for the knowledge and attitude tests, respectively. The findings revealed significant improvements in both knowledge and attitudes among participants. The mean knowledge score increased from 5.32 to 7.34 (p < 0.001), while the mean attitude score improved from 30.02 to 31.59 (p = 0.002). These results suggest that educational interventions can effectively enhance knowledge and develop positive attitudes toward health risk mitigation. Targeted educational interventions play a crucial role in improving knowledge and attitudes regarding occupational health risks among e-waste dismantling workers. Future research should evaluate the long-term impact of this intervention on safety practices and behavioral changes.